Analysis of Validation Development Science Learning Tools using Guided Inquiry Model Assisted by Real Media to Improve the Understanding Concepts and Science Process Skills of Students - Susilawati Susilawati; Aris Doyan; Putu Artayasa; Hary Soeprianto; Ahmad Harjono (Postgraduate, University of Mataram, 2021)
Development of natural science learning tools with guided inquiry model assisted by real media to improve students' mastery of science process concepts and skills has been successfully carried out. The purpose of this development is to produce a science learning tool guided Inquiry model assisted by valid real media. The development of these tools uses the 4D model (define, design, develop, and disseminate). Science learning tools developed in the form of syllabus, lesson plan implementation, student worksheets, science process skills instruments, and students' mastery of concepts. The results showed that the device validation process developed with the guided inquiry learning model fulfilled the content validation and construct validation. This suggests that it has produced a very valid device